MAKNA KOMUNIKASI SIMBOLIK TARIAN SUFI DI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO - Muhammad Ahsanul Faiz; Mohamat Hadori; A. Khairudin (Fakultas Dakwah Universitas Ibrahimy, 2026)
This study examines the symbolic communication meaning of Sufi dance at the Salafiyah Syafi'iyah Islamic Boarding School in Sukorejo, Situbondo. The method used in this study is qualitative, employing a case study approach. Sufi dance, commonly called Sema, is a sacred art form performed by some Sufis or Dervishes as they pursue the divine path to attain serenity, peace, and harmony of the soul. In the context of this research, we discuss a comprehensive overview of Islamic artistic practice, using systematic language for easy and comprehensive understanding. This approach aims to gain deeper insight into the data and information regarding Sufi dance performed at the Salafiyah Syafi'iyah Islamic Boarding School in Sukorejo, Situbondo. The results indicate that the Sufi dance represented is a mystical dance closely associated with spiritual meanings, reflected in several symbols within the dance process, such as the position of the hands raised upward as a symbol of prayer, and the position of the hands crossed over the chest, a symbol of shame.